2019
DOI: 10.3390/met9080899
|View full text |Cite
|
Sign up to set email alerts
|

Selective Milling and Elemental Assay of Printed Circuit Board Particles for Their Recycling Purpose

Abstract: Selective/preferential milling of printed circuit board (PCB) particles followed by non-destructive characterization of the mill products was performed in order to understand the effects of different feed masses into a hammer mill and different milling time on the metal recovery and enrichment ratio. Those are important variables affecting and determining the process performance and capacity. The milling tests and elemental assay characterization were conducted by using a hammer mill and a portable X-ray fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Thus, the general trend will be further discussed with the summary of liberation parameters given in Table 5. Despite being more liberated in the finest fractions in general, our previous studies [12,15] also showed the metals, especially Cu, were often enriched in coarser fractions (e.g., 1-2 mm) explained by selective agglomeration. Hence, the relationship among particle agglomeration, particle liberation and metallic enrichment is aimed to further understand in this study, and should be useful for further beneficiation stages.…”
Section: Determination Of Liberation Degree and Parametersmentioning
confidence: 75%
See 4 more Smart Citations
“…Thus, the general trend will be further discussed with the summary of liberation parameters given in Table 5. Despite being more liberated in the finest fractions in general, our previous studies [12,15] also showed the metals, especially Cu, were often enriched in coarser fractions (e.g., 1-2 mm) explained by selective agglomeration. Hence, the relationship among particle agglomeration, particle liberation and metallic enrichment is aimed to further understand in this study, and should be useful for further beneficiation stages.…”
Section: Determination Of Liberation Degree and Parametersmentioning
confidence: 75%
“…The above two trends were obtained with two other metal categories and other feed mass, in general, with some exceptions (e.g., Cu liberation degree decrease with size reduction with 80 g feed due to selective agglomeration, Figure 6c). operation although the highest recovery (40%) and enrichment (1.3) of Cu in that size fraction among all the milling conditions tested [15]. A further study of selective agglomeration and selective liberation will be of great interest in terms of practical use of agglomeration as a selective material recovery process.…”
Section: Determination Of Liberation Degree and Parametersmentioning
confidence: 87%
See 3 more Smart Citations